Identifying the Meaning of Colors as Design Information for Design Tools: A Systematic Literature Review - Swasty, Wirania; Utami, Lira Anindita; Ronggowarsito, Bimahadi Ilmawan; Yudiarti, Diena (Journal of Visual Art and Design, 2024)
The meaning of colors has been widely researched in various disciplines. In design, understanding the contextual meaning of color influences design decisions and, hence, is important design information. This research aimed to compile information about the meaning of colors that can be used as design information in design tools so that users can choose the right color palette. This research used a qualitative approach by conducting a contextual document review of reference books about color. Data collection was carried out by identifying relevant data regarding the meaning of colors. The data collected included color association, positive-negative meanings, and cultural links. Although the information derived from these three sources varied in terms of information themes, we could observe some consistent meanings shared by the sources. This research output can be implemented as design information in design tools such as web-based color palette generation applications, graphic design tools and others. It is hoped that the results of this research can provide comprehensive guidance in choosing an appropriate color palette based on the meaning of the colors contained.